Sleepy Time Olie - Joyce, William (New York : Laura Geringer Books/HarperCollins Publishers, 2001)
When Pappy bumps his head before bedtime, Olie cheers him up by inventing a super silly ray, and then they both become happy, sleepy robots.
Keywords: Robots -- Fiction; Inventions -- Fiction; Bedtime -- Fiction; Stories in rhyme